Preparation of amphoteric polycarboxylate superplasticizers and their performances in cementitious system. Issue 4 (27th August 2014) - Jiang, Lingfei; Kong, Xiangming; Lu, Zichen; Hou, Shanshan
ABSTRACT A series of amphoteric polycarboxylate (PC) polymers were synthesized by radical copolymerization of acrylic acid (AA), [3‐(methacryloylamino) propyl] trimethylammonium chloride (MAPTAC) and ω‐methoxypolyoxyethylene methacrylate ester (MPEGMA). Cationic groups were introduced in to PC molecules with expectation of less retardation effect on cement hydration compared to the traditional anionic PC superplasticizers. The content of cationic groups in polymer was varied by changing the monomer ratio of MAPTAC to AA in the synthesis recipes. The structure of the synthesized amphoteric PCs was verified by gel permeation chromatography (GPC) and Fourier transform infrared spectroscopy (FTIR). The performances of the amphoteric PCs were evaluated by measurement of flowability and zeta‐potential of cement pastes and adsorption amount of PC in cement pastes. Impacts of the PCs on cement hydration were studied by isothermal calorimetry. It is concluded that both anionic and cationic PC polymers can be effectively adsorbed onto the surface of cement particles and thus change the zeta potential of cement pastes. The adsorption amounts of the amphoteric PCs decrease with increasing content of cationic units. A proper incorporation of cationic units into PC polymers may lead to a higher fluidizing performance in fresh cement pastes. The amphoteric PC polymers with higher content of cationic units show less retardation effect on cement hydration and hence higher early strength of cementitious materials may be achieved by using amphoteric PCs with appropriated content of cationic units without losing their plasticizing efficiency. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41348.